Coupled Multipath BBR (C-MPBBR): A Efficient Congestion Control Algorithm for Multipath TCP - Imtiaz Mahmud; Tabassum Lubna; Yeong-Jun Song; You-Ze Cho (IEEE Access, 2020)
Multipath transmission control protocol (MPTCP) is a promising transport layer protocol that enables a device to utilize multiple communication interfaces simultaneously, thereby achieving high throughput. A congestion control algorithm (CCA) employed in MPTCP constitutes a key part that controls the data flow through different subflows (SFs). There are two fundamental challenges associated with MPTCP CCAs. First, MPTCP flows should have an advantage over single-path flows; second, MPTCP flows should be fair, indicating that SFs sharing a common bottleneck should occupy a capacity fairly close to that occupied by a single-path flow. Several MPTCP CCAs have been developed; however, they have failed to satisfy these challenges in all scenarios. Recently, Google has introduced the bottleneck bandwidth and round-trip-time (BBR), a new CCA for single-path TCP, achieving high throughput with minimum delay by employing a network model. In the present paper, we propose a novel MPTCP CCA based on BBR named coupled multipath BBR (C-MPBBR) that satisfies the fundamental challenges by exploiting the concept of network modeling in BBR. C-MPBBR addresses the first challenge by closing the low-bandwidth SFs by tracking the delivery rate and bottleneck bandwidth (BtlBW). Then, it satisfies the second challenge through identifying those SFs that share a common bottleneck and dividing the BtlBW share corresponding to a SF among them. We implemented C-MPBBR in the Linux kernel, tested it on a wide range of scenarios by the Mininet emulation experiments, and the real-world Internet, and confirmed that the proposed C-MPBBR outperforms the existing MPTCP CCAs in terms of successfully satisfying the fundamental challenges by ensuring both throughput and fairness.